2022
DOI: 10.1016/j.esmoop.2021.100343
|View full text |Cite
|
Sign up to set email alerts
|

How we treat patients with metastatic HER2-positive breast cancer

Abstract: HER2-positive breast cancer represents 15%-20% of breast malignancies and is characterized by an aggressive behavior and high recurrence rates. Anti-HER2-directed agents represent the mainstay of treatment of patients with HER2-positive metastatic breast cancer (MBC). In this review we propose a treatment algorithm for patients with HER2-positive MBC based on the currently available literature on the topic. The combination of trastuzumab, pertuzumab and a taxane (THP) remains the preferred first-line therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 18 publications
1
34
0
5
Order By: Relevance
“…Particularly, the HER2CLIMB trial also included patients with active (progressive and/or untreated) BCBM [ 27 ]. In view of the gratifying outcomes, neratinib plus capecitabine and the tucatinib–trastuzumab–capecitabine triplet are recommended for the later-line treatment for HER2-positive BC in metastatic setting, especially for patients with CNS disease [ 53 ]. In this NMA, we focused on the BCBM subgroup of the original studies.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the HER2CLIMB trial also included patients with active (progressive and/or untreated) BCBM [ 27 ]. In view of the gratifying outcomes, neratinib plus capecitabine and the tucatinib–trastuzumab–capecitabine triplet are recommended for the later-line treatment for HER2-positive BC in metastatic setting, especially for patients with CNS disease [ 53 ]. In this NMA, we focused on the BCBM subgroup of the original studies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these premises, the most updated international guidelines recommend the dual blockade with trastuzumab – pertuzumab plus docetaxel as the first-line standard in treatment-naïve HER2-positive BC patients with metastatic disease, regardless of hormone receptor status. 14 , 15 Docetaxel should be given for at least 6 cycles, if tolerated, followed by maintenance trastuzumab and pertuzumab until disease progression; after completing at least 6 cycles of upfront concomitant chemotherapy, endocrine treatment may be added to trastuzumab and pertuzumab maintenance therapy for patients with HER2-positive, hormone-receptor positive tumors. 14 , 15 In case of significant comorbidities, advanced age, and/or poor performance status in BC patients with hormone-receptor positive disease, endocrine treatment combined with a HER2-targeted therapy may be used.…”
Section: First-line Treatmentmentioning
confidence: 99%
“… 14 , 15 Docetaxel should be given for at least 6 cycles, if tolerated, followed by maintenance trastuzumab and pertuzumab until disease progression; after completing at least 6 cycles of upfront concomitant chemotherapy, endocrine treatment may be added to trastuzumab and pertuzumab maintenance therapy for patients with HER2-positive, hormone-receptor positive tumors. 14 , 15 In case of significant comorbidities, advanced age, and/or poor performance status in BC patients with hormone-receptor positive disease, endocrine treatment combined with a HER2-targeted therapy may be used. Lastly, the use of single-agent endocrine therapy without an anti-HER2 agent is not routinely recommended unless cardiac disease could preclude the safe use of HER2-directed treatments.…”
Section: First-line Treatmentmentioning
confidence: 99%
“…HER2+ BCBM may be endocrine resistant and consequently immune to therapies that target hormone receptor-positive breast cancer, such as tamoxifen and fulvestrant. One first-line treatment for HER2+ BCBM is taxane, trastuzumab, and pertuzumab [ 60 , 61 ]. Trials have indicated that while the monoclonal antibody pertuzumab may have a low blood-brain barrier (BBB) permeability, the concentration in the central nervous system (CNS) is enough to produce a significant therapeutic effect [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…One first-line treatment for HER2+ BCBM is taxane, trastuzumab, and pertuzumab [ 60 , 61 ]. Trials have indicated that while the monoclonal antibody pertuzumab may have a low blood-brain barrier (BBB) permeability, the concentration in the central nervous system (CNS) is enough to produce a significant therapeutic effect [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%